THE LACK OF INTEREST IN LOAN ACQUISITION AMONG UNIVERSITY STUDENT ENTREPRENEURS - Alias, Mohd Azuan Mohd; Hasan, Zakiyah; Nik Roseley, Nik Roselina; Ikhsan, Nurzaki (JURNAL SIGNAL, 2024)
The critical role of entrepreneurship in stimulating innovation and fostering economic growth is well-recognized in academic and policy circles. Specifically, university student entrepreneurs represent a dynamic demographic that contributes to this financial and innovative drive. Student entrepreneurs often face considerable challenges in starting and growing their businesses despite their potential. One of the key obstacles is the procurement of necessary capital to fund their entrepreneurial ventures. While many financial institutions offer a variety of loan schemes specifically designed to facilitate entrepreneurship, there is a noticeable reluctance among student entrepreneurs to take advantage of these financial products. Few studies have investigated the reasons for and consequences of this hesitation towards these financing mechanisms within academic institutions. This paper proposes a conceptual research framework related to the issue of lack of interest in loan acquisition among student entrepreneurs, a complex problem with potential long-term implications. The framework situates acquiring and using information within several contextual factors. By investigating the factors behind this lack of interest, this study aims to understand better student entrepreneurs’ financial behaviours, which could inform the design of financial products and support measures that cater to their specific needs. This research has the potential to significantly impact the strategies of financial institutions, policymakers, and university entrepreneurship programs, ultimately fostering the growth of student entrepreneurship. Keywords: Factors, Lack of Interest, Role of Loan, Loan Acquisition, Student Entrepreneurs